Diversity in Social Support Among Young Justice Involved Parents - Lloyd, Kristin M. (Journal of developmental and life-course criminology, 2024)
Adolescence is marked by incredible change that impacts the life-course. One change that may have profound impacts is teen parenthood. Having access to emotional support may act as a protective factor that reduces negative outcomes, yet little is known about teen parents’ access to such support. Accordingly, using data from the Pathways to Desistance Study, the current study examines how becoming a teen parent changes the number of supportive adults this group had access to (diversity of support). Further, the current study examines the extent to which gender impacts the ability for justice involved youth to leverage support. Results indicate that justice system involved teen parents have access to fewer supportive persons after they become parents. The same is true for residential parents—those who lived with their child—and young mothers.